EFEKTYWNOŚĆ JAKO DETERMINANTA KAPITALIZACJI BANKÓW SPÓŁDZIELCZYCH W POLSCE W ŚWIETLE ZAŁOŻEŃ NOWEJ UMOWY KAPITAŁOWEJ KOMITETU BAZYLEJSKIEGO - Mielnik, Mariusz; Ławrynowicz, Maciej; Szambelańczyk, Jan (Wydział Prawa i Administracji UAM, 2004)
Since 1996 a lot of work and research has been devoted to the New Capital Accord (NCA — Accord II) which is to replace the current one, dated 1998. Main modifications include: introduction of the capital minimum for operating risk and interest rate in the bank portfolio, wider scope of weighs while determining credit risk as well changes to the methodology of determining capital adequacy on ratings of respectable agencies or, as an important novelty - internal ratings of crediting institutions.
EFFICIENCY AS A DETERMINING FACTOR OF CAPITALIZATION OF COOPERATIVE BANKS IN POLAND IN THE LIGHT OF ASSUMPTIONS TO THE NEW CAPITAL ACCORD OF THE BASEL COMMITTEE